Nuclear Receptor Corepressor 1 expression and output declines with prostate cancer progression - Lopez, Sandra M. (Clin Cancer Res, 2016)
PURPOSE: Castration therapy in advanced prostate cancer eventually fails and leads to development of castration resistant prostate cancer (CRPC) which has no cure. Characteristic features of CRPC can be increased androgen receptor (AR) expression and altered transcriptional output. We investigated expression of Nuclear Receptor Corepressor 1 (NCOR1) in human prostate and prostate cancer and the role of NCOR1 in response to antiandrogens. EXPERIMENTAL DESIGN: NCOR1 protein levels were compared between matched normal prostate and prostate cancer in 409 patient samples. NCOR1 knockdown was used to investigate its effect on bicalutamide response in androgen-dependent prostate cancer cell lines and transcriptional changes associated with loss of NCOR1. NCOR1 transcriptional signature was also examined in prostate cancer gene expression datasets. RESULTS: NCOR1 protein was detected in cytoplasm and nuclei of secretory epithelial cells in normal prostate. Both cytoplasmic and nuclear NCOR1 protein levels were lower in prostate cancer than in normal prostate. Prostate cancer metastases show significant decrease in NCOR1 transcriptional output. Inhibition of LNCaP cellular proliferation by bicalutamide requires NCOR1. NCOR1 regulated genes suppress cellular proliferation and mediate bicalutamide resistance. In mouse, NCOR1 is required for bicalutamide dependent regulation of a subset of the AR target genes. CONCLUSIONS: In summary, we demonstrated that NCOR1 function declines with prostate cancer progression. Reduction in NCOR1 levels causes bicalutamide resistance in LNCaP cells and compromises response to bicalutamide in mouse prostate in vivo.